Kualitas Benih Berdasarkan Warna Kulit dan Bagian Buah, serta Kualitas Bibit Srikaya dengan Pemberian PGPR dan CaCO3 - Riski Meliya Ningsih; Widajati, Eny; Endah Retno Palupi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2021)
Srikaya’s high quality seeds are needed to support development of srikaya. This study aimed to determine the level of maturity and position of the seeds in the fruit in order to get quality seeds and get the best treatment to improve seedling performance through the use of rhizobacteria and CaCO3. The first experiment used a two-factor completely randomized design (CRD), with the first factor of the color of the exocarp of the fruit and the second factor of the position of the seed in the fruit. The second experiment used CRD with rhizobacteria, CaCO3, and a combination of both as a single factor. The first count time was observed for germination at 36 days after planting (DAP) and the final count was at 56 DAP. The best seed quality was obtained from the yellow exocarp color based on seed dry weight, germination, vigor index, normal germination dry weight, and seed growth speed. The highest seed growth vigor was obtained from fruit with yellow exocarp color from the tip and base of the fruit. CaCO3 treatment affected root elongation, leaf width, stem diameter, and leaf length. Application CaCO3 gives the best effect on seedling growth followed by Pseudomonas + Actimomycetes + CaCO3 treatment. Keywords: Annona squamosa, rootstock, final count, vigor index, rhizobacteria